VD_FINDINFO Jug / 2018 / 28 vom 23. Mai 2017 - VD Tribunal cantonal (2017)
MOYEN DE PREUVE, LÉSION CORPORELLE PAR NÉGLIGENCE, LÉSION CORPORELLE GRAVE, FAUTE PROPRE, ACTE D'ACCUSATION | 12 al. 3 CP, 125 CP, 139 CPP (CH), 325 al. 1 CPP (CH), 429 al. 1 let. a CPP (CH), 9 CPP (CH)